2011
DOI: 10.1001/archgenpsychiatry.2011.72
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Divalproex Sodium to Attenuate Agitation and Clinical Progression of Alzheimer Disease

Abstract: Valproate treatment did not delay emergence of agitation or psychosis or slow cognitive or functional decline in patients with moderate Alzheimer disease and was associated with significant toxic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
109
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(118 citation statements)
references
References 47 publications
3
109
0
3
Order By: Relevance
“…The primary clinical endpoint was time to emergence of agitation or psychosis, combined with an assessment of the clinical significance of behavioral change rated by the study clinician. 11 Structural MRI scans were acquired at baseline and at 12 months to assess treatment and disease-associated changes in whole brain, hippocampal, and ventricular volumes over time, as a planned secondary analysis in a subset of participants. Randomization was one-toone for the 2 treatment groups in permuted blocks of 4.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The primary clinical endpoint was time to emergence of agitation or psychosis, combined with an assessment of the clinical significance of behavioral change rated by the study clinician. 11 Structural MRI scans were acquired at baseline and at 12 months to assess treatment and disease-associated changes in whole brain, hippocampal, and ventricular volumes over time, as a planned secondary analysis in a subset of participants. Randomization was one-toone for the 2 treatment groups in permuted blocks of 4.…”
Section: Methodsmentioning
confidence: 99%
“…Time to emergence of agitation or psychosis was assessed using the Neuropsychiatric Inventory (NPI). 11,13 Secondary clinical aims included delaying the progression of cognitive, functional, other behavioral and global measures associated with AD. These secondary aims were assessed with the Alzheimer's Disease Assessment Scale-cognitive subscale (ADAS-cog), the Clinical Dementia Rating (CDR), MMSE, ADCS activities of daily living (ADCS-ADL), the ADCS Clinical Global Impression of Change scale (ADCS-CGIC), Cohen Mansfield Agitation Inventory (CMAI), and the Alzheimer's Disease Quality of Life scale (QOL-AD).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Valproic acid, a treatment for epilepsy and bipolar disorder, showed preclinical efficacy with diverse mechanisms [87][88][89][90]. However clinical studies showed no beneficial effects in AD [91,92].…”
Section: Antiepileptic Drugsmentioning
confidence: 99%